Vitória na derrota: Álvaro Alberto e as origens da política nuclear brasileira - Pereira, Leandro da Silva Batista (2013)
The present work covers the first years of the Brazilian nuclear policy, betwee n 1945 and 1956. Our aim is to understand the reasons of the triumph of Admiral Álvaro Alberto in the 1956 Parliamentarian Inquiry Commission of the Nuclear Question (CP I da Questão Nuclear), in which his policy proposals for the nuclear sector were vindicated and re-established, even after the personal defeats suffered by him during the Café Filho Administration (1954-1955), when he was fired from the presidency of the CNPq and witnessed his nuclear policy being stopped by the government. The work concludes that such an outcome was made possible by the fact that his guidelines for the nuclear sector managed to obtain a significant echo among several sectors of the Brazilian society that defended the state monopoly on the natural resources and an autonomous scientific and technological development effort. Besides that, his efforts were aided by an exceptionally favorable political conjuncture at the earl y phase of the Juscelino Kubitschek Administration (1956-1961), which was distinguished by a st rong political polarization, in which the nuclear question gained a national projec tion. With his triumph in the 1956 CPI, Alberto managed to define the terms of the debat e about the nuclear policy in the following years and decades.